Designing e-learning based independent learning activity unit through virtual worksheet: improving student's 4Cs. (June 2020) - Aziziy, Y N; Sulhadi,; Marwoto, P; Iswari, R S
Abstract: The subject of Physics at Sumenep Senior High School grounded in 4C's (Communication, Collaboration, Critical Thinking, Creativity) has not yet been deliberately developed because of the lack of learning tools oriented in the 4C's. Independent Learning Activity Unit (UKBM) as teaching systems that develop 4C's can be used to enable students to solve problems. In this research was to create e-Learning Independent Learning Activity Unit teaching are developed through Virtual Worksheet which can improve the student 4C's. The development of teaching tools was conducted in five major steps (Analysis, Design, Development, Implementation, Evaluation). The characteristics of the UKBM e-Learning are developed through problems on a virtual worksheet, which must be solved by students. This study material is centered around students and must be completed individually and in groups. The results showed that teaching systems were valid. The effectiveness of teaching systems based on concept understanding was increased by an average N-gain of experimental class which are respectively classified as high category. The feasibility of the teaching systems on the treated (experiment) class from the first until the seventh meeting was in a good category. The teacher and students responded positively to the teaching systems in the classroom.